2019
DOI: 10.21580/vjv8i13280
|View full text |Cite
|
Sign up to set email alerts
|

The ICT Used by the English Lecturers for Non English Study Program Students at STAIN Curup

Abstract: <p>This research is done by the researcher to investigate kinds of ICT used by English lecturers for non-English Study Program students at IAIN Curup and to investigate the roles of ICT for the English lecturer at IAIN Curup. This research used descriptive quantitative Because the questioner's results were evaluated and explained in the explanatory form.The questionnaire used as the instrument to collect the data. Questionnaire about the ICT used by the English lecturers for non-English Study Program stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 7 publications
(8 reference statements)
4
17
0
Order By: Relevance
“…The majority of the students (89%) find CALL an effective strategy for saving time in the learning process, providing instant feedback on their drills and learning autonomy. It is same findings with Apriani and Hidayah (2019),she found that ICT (CALL one of them) can saving time in teaching and learning process. Besides, they find computer as a tutor guiding them.…”
Section: Paulsupporting
confidence: 76%
“…The majority of the students (89%) find CALL an effective strategy for saving time in the learning process, providing instant feedback on their drills and learning autonomy. It is same findings with Apriani and Hidayah (2019),she found that ICT (CALL one of them) can saving time in teaching and learning process. Besides, they find computer as a tutor guiding them.…”
Section: Paulsupporting
confidence: 76%
“…Online learners had positive perceptions [5] in their learning process when the Covid pandemic happened. The good points expressed were not excluded: (1) learners enable to continuously maintain their learning courses and promptly graduate from the university if they have no problems with internet access, financial issue, and online learning implementation; (2)learners enable to complete their tasks well without physical learning on campus and require more small group tasks in order to they could support their friends who did not have an internet pulse and access [1]; (3) learners enable to improve their English ability and their characteristics thanks to the application of ICT in the online learning process, [45]. Overall, both learners and teachers expressed their positive attitudes toward applying technological advances and ICT development in English training in remote settings [1,5,26,30,33].…”
Section: Learners' Perceptions In Online Learning During Covid-19 Periodmentioning
confidence: 99%
“…The function of the academic portal for lecturers is the timeliness of starting and ending classes, managing student grades, checking student attendance, gathering material and information about lectures, and checking and approving student form of study plan. Academic functions for students are filling form of study plan online, Drafting team of IAIN Curup, [1]; [6]; [21]; [36]; [37] sending form of study result online, seeing online grades and seeing assignments or information about campus and lectures.…”
Section: The Effect Of Academic Portal Use Of Lecturer's Performancementioning
confidence: 99%